Pengaruh Pengembangan Pegawai on the Job Training dan Kedisplinan Kerja Terhadap Peningkatan Kinerja di BKD Kabupaten Gresik - Lilik Nurcholidah; Indira Sofia; Muhammad Chusnul Khitam (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This research was conducted to see the effect of ON THE JOB TRAINING Employee Development and Work Discipline on Performance Improvement in BKD Gresik Regency. The hypothesis has a simultaneous, partial and relatively dominant effect on the performance improvement. With the sample used is a number of 50 employees. From the results of the t-test of the Employee Development On The Job Training (X1) variable on Performance Improvement (Y), the results obtained a significant level of 0.000 <0.05 and tcount of 4.614 t table of 2.0129. From these data, the value of tcount > ttable (4.614 > 2.0129), it can be concluded that partially the Employee Development variable has a significant effect on Performance Appraisal. And the variable of Work Discipline (X₂) on Performance Improvement (Y) obtained the results of a significant level of 0.000 < from 0.05 and tcount of 2.762 ttable of 2.0129. From these data, the value of tcount > ttable (2.762 > 2.0129), it can be concluded that partially the price variable has a significant effect on Performance Improvement. Fcount (40.966) > Ftable (2.8086) with a significance of 0.00 which indicates that it simultaneously has an effect. And the most dominant variable is the Employee Development On The Job Training (X1) variable because it has the highest value of 0.421.